Are children with unrecognised psychiatric disorders being excluded from school? A secondary analysis of the British Child and Adolescent Mental Health Surveys 2004 and 2007. Issue 15 (20th December 2018) - Parker, Claire; Tejerina-Arreal, María; Henley, William; Goodman, Robert; Logan, Stuart; Ford, Tamsin
Abstract: Background: There is limited research that explores the association between exclusion from school and mental health, but it seems intuitively plausible that the recognition of mental difficulties by key teachers and parents would influence the likelihood of exclusion from school. Methods: A secondary analysis of the British Child and Adolescent Mental Health survey 2004, ( n = 7997) and the 2007 follow-up ( n = 5326) was conducted. Recognition of difficulty was assessed via a derived variable that combined the first item of the Impact supplement of the Strengths and Difficulties Questionnaire which asked parents and teachers if they thought that the child has difficulties with emotions, behaviour and concentration, and the presence/absence of psychiatric disorder measured by the Development and Well-being Assessment. Results: Adjusted logistic regression models demonstrated that children with recognised difficulties were more likely to be excluded [adjusted odds ratio (OR) 5.78, confidence interval 3.45–9.64, p < 0.001], but children with unrecognised difficulties [adjusted OR 3.58 (1.46–8.81) p < 0.005] or recognised subclinical difficulties [adjusted OR 3.42 (2.04–5.73) p < 0.001] were also more likely to be excluded than children with no difficulties. Children with conduct disorder and attention deficit hyperactivity disorder were most likely to be excluded compared with other types of disorder. Conclusion: Exclusion from school may result from a failure to provide timely and effective support rather than a failure to recognise psychopathology.